The social media framing of gender pay gap debate in American women's sport: A linguistic analysis of emotive language - Reem Alkhammash (Peoples' Friendship University of Russia (RUDN University), 2021)
Coverage of the United States women's national soccer team (USWNT) winning the FIFA Women's World Cup flooded social media in the summer of 2019. Their immense achievement led many members of the team to take the opportunity to highlight gender inequality in sport, particularly the wage discrepancy between male and female athletes. Social media coverage of the issue stirred a discussion between supporters and opponents of equal pay for female athletes. A call for change is evident in the speeches and interviews of members of the football team. This was followed by a social media call for gender equality in sport. This study investigates the emotive language used to advocate for equal pay for US women soccer players in social media. The data were collected for one month following the USWNT's winning the Women's World Cup in 2019 and comprise a corpus of more than ten thousand tweets. The corpus has more than one million words. The distribution and the valence of emotive language were quantified. The data was subjected to both computational and qualitative analyses of emotive language. The findings of quantitative analysis included positive and negative language as the emotional valence was reported. In the qualitative analysis, it is found that positive language is used to express pride in the achievement and to show support of the team members' endeavour to end the gender pay gap. However, negative language included disappointment in the official organisations thought to be responsible for the gender pay gap. Thus, the emotive language indicates the specific situational context and the role of athletes as cultural artefacts in calls for change. At the same time, emotive language is prevalent in social media, and it has an important role in narratives of gender inequality in the US.